BEHAVIOURAL PROBLEMS AMONG DOWN SYNDROME CHILDREN: AN INTERVENTION-BASED STUDY - Atta, Huma; Rehman, Ishrat; Umair, Muhammad (Annals of Allied Health Sciences, 2024)
Objective: To find out the effectiveness of Dr. Stein behavioural modification strategies among Down syndrome children’s behavioural problems. Material & Methods: We took a group of individuals (aged 8-16) having Down syndrome from national special education complex, Peshawar. They were assessed through the behavioural problem index to give us an idea on their behaviour problems, those with a behavioural problem were kept in therapy for further sessions to help them improve. Results: A treatment plan was made according to the extracted behavioural problems of Down syndrome children. Dr. Stein recommended behavioural modification treatment strategies were used for behavioural modification of Down syndrome children (Routine, reward, choice, redirection and consistency). Pre-intervention (M=69.11, SD=6.27) and post-intervention (M=61.33, SD=6.51) conditions; t (8) =2.70, p=0.027. Conclusion: After the successful completion of 9 sessions with Down syndrome children, their behavioural problems were reassessed. Results indicated that Dr. Stein behavioural modification strategy is an effective treatment plan for the modification of behavioural problems among Down syndrome children.